PENGARUH PENAMBAHAN SUPERPLASTISIZER TERHADAP CAMPURAN BETON RINGAN YANG MENGGUNAKAN STYROFOAM - Kusnadi, Kusnadi; Sulistyorini, Dewi (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2015)
The risk of failure of structures effect of earthquake be high due to the heavy volume of concrete has a fairly high (2400 kg/m3). Advances in technology and the impact of the economic crisis encourage construction of infrastructure use concrete masonry units under 1900 kg/m3 in weight. The use of lightweight concrete is the filler material styrofoam intend at non structural components like wall. One of the problem of making lightweight concrete using styrofoam is the low value of slump, so that the mix becomes difficult (low workability). It is therefore necessary to add material superplastisizer This research used 20 cylinder test samples. The composition of the mixture consists of sand, cement and grain of styrofoam. The styrofoam in concrete is 20% in volume. The Sample variation consists of light weight concrete using styrofoam without superplastisizer is four cylinder, with added superplastisizer four cylinder were 0.5%, 1.0%, 1.5% and 2%, respectively in weight of cement. The results showed the addition of superplastisizer 0.5%, 1%, 1.5% and 2% of the cement weight increases the value of slump were 100%, 183%, 216% and 507% respectively. The addition of superplastisizer 0.5%, 1%, 1.5% and 2% of the cement weight increase ceompression strength were 8.48% 4.25%, 12.67% and 17.37% respectively. The addition of superplasticizer will increases the slump for the same water content in fresh concrete, so can increase the compressive strength of concrete cylinder. Keyword : beton styrofoam, workabilitas, superplasticizer